(untitled) (Estudios Gerenciales, 2004)
The purpose of this investigationwas to simulate a real life scenarioand explore the way economicagents update their beliefs. Do theyupdate according to what theyhope? Or do they update inspired byrational behavior?We mimicked the environment whicha recently high school graduate faceswhen entering college to see how astudent updates his beliefs in regardsto his classroom position. We examinedhow economic agents envisagethemselves through and through collegeand see if they update their beliefsabout a hypothesis A in the lightof new evidence B, or if they updatetheir beliefs subject to what theychoose they hope. In this sense weexplored the possibility of setting asidethe neoclassical assumption thatagents are anything more than hyperrational naïve optimizers acting on perfect (and in some cases, limited information)in order to turn back to anolder tradition in economic theory, thatis agents are recognizably human.